1999
DOI: 10.1111/j.1365-2141.1999.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell membrane disorders

Abstract: The red blood cell membrane is a multi-component structure that is responsible for many of the physiological functions and mechanical properties of the cell. Defects in any of these components can manifest as clinical disorders involving the erythrocytes. In the past few years there have been major advances in our understanding of the molecular basis of these disorders, in which mutational analysis has clarified many questions about the structure-function relationship of components of the red cell membrane. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
236
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(244 citation statements)
references
References 124 publications
4
236
0
4
Order By: Relevance
“…This relation agrees well with data showing that spherocytotic RBCs have a greater osmotic fragility (3). In spherocytosis, a patient's RBCs assume a spherical shape due to defects in RBC membrane-associated cytoskeletal proteins (4,5). However, osmotic fragility measurements on spherocytotic cells leave open the possibility that osmotic fragility is not due to cell shape alone, but to differences between the cytoskeletal makeup of spherocytotic and normal RBCs.…”
Section: Lifetime Dependence On Cell Shapesupporting
confidence: 88%
See 1 more Smart Citation
“…This relation agrees well with data showing that spherocytotic RBCs have a greater osmotic fragility (3). In spherocytosis, a patient's RBCs assume a spherical shape due to defects in RBC membrane-associated cytoskeletal proteins (4,5). However, osmotic fragility measurements on spherocytotic cells leave open the possibility that osmotic fragility is not due to cell shape alone, but to differences between the cytoskeletal makeup of spherocytotic and normal RBCs.…”
Section: Lifetime Dependence On Cell Shapesupporting
confidence: 88%
“…It has been shown that the osmotic fragility of spherocytic RBCs is higher than that of normal-shaped RBCs (3). However, spherocytic RBCs have a cytoskeletal protein makeup different from that of normal RBCs (4,5), a factor that could influence osmotic fragility independent of cell shape effects. It is therefore important to determine the relation between cell shape and alkaline hemolysis fragility (and osmotic fragility) for healthy RBCs.…”
mentioning
confidence: 99%
“…In the Northern European population, it is the most-common, inherited form of anemia, affecting approximately 1 in 1,000-2,500 individuals. In nearly 75 % of cases, the inheritance has an autosomal dominant pattern, and the other 25 % of cases present recessive forms and de novo mutations [1][2][3]. HS syndromes are a group of inherited disorders characterized by the presence of spherical-shaped erythrocytes on the peripheral blood smear [4].…”
Section: Introductionmentioning
confidence: 99%
“…It results from the deficiency or dysfunction of one of the red blood cell membrane proteins such as a spectrin, b spectrin, ankyrin, an anion channel protein (Band-3 protein), Protein 4.1 and Protein 4.2 (1). Diagnosis of moderate to severe forms of hereditary spherocytosis and other membrane disorders like hereditary elliptocytosis (HE) and hereditary pyropoikilocytosis is conventionally done by a series of investigations which include peripheral smear examination, reticulocyte count, red cell indices, osmotic fragility, autohemolysis test, and acidified glycerol lysis test after exclusion of other hemolytic conditions like hemoglobinopathies, red cell enzymopathies, and autoimmune hemolytic anemia (2,3).…”
mentioning
confidence: 99%